Bilateral Optic Disc Pit, Bilateral Iris Chorioretinal Coloboma and Unilateral Congenital Ptosis in a Person with Persistent Patent Ductus Arterious: A Rare Case with Review of Literatures - Thapa, Raba (Archives of Clinical and Medical Case Reports, 2020)
We report a 24 year old female presented with drooping of left eye upper lid since birth. Examination revealed left eye upper lid congenital ptosis, both eyes iris, chorioretinal coloboma and both eyes optic disc pit. Her medical records showed ligation of patent ductus arteriosus in her childhood. The ductus arteriosus closes soon after birth, but sometimes it fails to close leading to persistent patent ductus arteriosus. Optic disc pit, iris chorioretinal coloboma and congenital ptosis are among the rare congenital anomalies of eye. We report this case because of its rarity with review of literatures.